Intensive intervention for children and adolescents with autism in a community setting in Italy: a single-group longitudinal study - Valenti Marco; Cerbo Renato; Masedu Francesco; De Caris Marco; Sorge Germana (BMC, 2010)
Abstract Background Previous studies have shown favourable results with intensive behavioural treatment for children with autism: evidence has emerged that treatment can be successfully implemented in a community setting and in adolescent participants. The aim of this study was to describe the 2-year adaptive functioning outcome of children and adolescents with autism treated intensively within the context of special autism centres, as well as to evaluate family satisfaction with the activity of the centres. Methods Sixty participants with autism (20 females and 40 males, aged between 4 and 18 years) attending the semi-residential rehabilitation centres for autism located in the Abruzzo region (Central Italy) were followed up and their adaptive functioning was evaluated both at baseline and after one and two years using the Vineland Adaptive Behaviour Scales (VABS). Parents' satisfaction with the service was evaluated using the Orbetello Satisfaction Scale for Children and Adolescent Mental Health. Results The increase in VABS scores was significant on several domains in the different gender and age categories. It is worth noting that male children had improved a great deal (roughly, an effect size >0.20) in the domains of communication, daily living and motor skills (effect sizes 0.34, 0.45 and 0.27 respectively) whereas in male adolescents, a notable increase in VABS scores was recorded in the domain of socialization only (effect size 0.23). On the other hand, adaptive behaviour in female children increased in the domains of socialization and motor skills (effect sizes 0.27 and 0.42 respectively) whereas in female adolescents, good results were achieved in the domains of daily living, socialization and motor skills (effect sizes 0.22, 0.26 and 0.20 respectively). The level of satisfaction of users of the service over time was found to be substantial, even when they had recently started the program. Conclusions Our results support the implementation of special autism treatment community centres, based on a parent co-directed rehabilitative, intensive and early intervention. Further experimental research designed to document the effectiveness of services provided to children and adolescents with autism in the community is recommended.